How does the volunteer experience at the Paris2024 Olympics impact the awareness, the perception and perceived quality of Olympic sponsors among volunteers? - Weisen, Jo (Πανεπιστήμιο Πελοποννήσου, 2025)
This thesis delves into how volunteering at the Paris2024 Olympic Games influences volunteers’ awareness, perception, and perceived quality of Olympic sponsors. The literature review of this thesis delves into the concepts of brand and brand equity, with a focus on brand awareness, brand image and brand perception. Understanding these elements is crucial for analyzing the Olympic brand and the structure and function of Olympic sponsorships. The literature also dives into how Olympic marketing is done and the differences of worldwide and domestic Olympic sponsor programmes. Aaker’s brand equity model serves as the theoretical framework for this study, enabling a better understanding of how the volunteer experience at the Paris2024 Olympic Games influences the awareness and perception of Olympic sponsors among volunteers. Data was collected through an online bilingual survey, ensuring wide participation and making the findings more universally applicable. The study included a pilot testing with a diverse group of volunteers, which helped refine the survey and ensured it was clear and effective. The results show that volunteer experiences significantly impact brand awareness, with high recall and recognition rates. Major sponsors like Coca Cola and VISA, known for their long standing Olympic partnership, received particularly more brand awareness. Among domestic sponsors, Decathlon stood out by providing volunteer uniforms, demonstrating how consistent and visible engagement can elevate brand awareness among volunteers. However, the impact on brand perception and perceived quality was more nuanced. Volunteers showed a slight positive bias towards Olympic sponsors, recognizing the prestigious image. Important to note that the research results represent volunteers’ self-perception, which may differ from their actual behavior. The findings highlight a gap between brand association formed through visibility and the trust needed to drive purchasing decisions aligning with Aaker’s emphasis on the importance of perceived quality. The research suggests that sponsors should strategically combine Olympic brand visibility with quality demonstrations to bridge the gap between awareness and consumer action. This thesis underscores the importance of strategically aligning sponsorship practices with volunteer experiences. It concludes by emphasizing the need for further research to deepen understanding of sponsor-volunteers dynamics and to explore the long-term impacts on brand perception and volunteers satisfaction, offering a foundation for optimizing sponsor engagement with volunteers in future Olympic events.
Keywords: Ολυμπιακοί αγώνες - Μάρκετινγκ; Ολυμπιακοί αγώνες - Παρίσι 2024; Αθλητισμός - Μάρκετινγκ; Εθελοντισμός; Εθελοντές; Αθλητική χορηγία; Olympics - Marketing; Olympics - Paris 2024; Sports - Marketing; Voluntarism; Volunteers; Sports sponsorship; Olympic Sponsorship; Brand Equity; Brans Awareness; Brand Perception; Perceived Quality; Volunteers; Paris2024